IMPLEMENTASI MANAJEMEN PEMBIAYAAN DALAM MENGEMBANGKAN SARANA DAN PRASARANA DI SMP HASBUNALLAH KABUPATEN TABALONG - Miranti Miranti (ADIBA : JOURNAL OF EDUCATION, 2023)
The implementation of financing management in developing good facilities and infrastructure is highly expected, because with good existing management it will support better school performance, so that the vision and mission of the school can be realized. Based on this statement, the formulation of the problem in this study is how is the implementation of financing management in developing facilities and infrastructure at SMP Hasbunallah? The goal to be achieved is to find out the implementation of financing management in developing facilities and infrastructure at SMP Hasbunallah. This type of research is field research and the approach taken is a qualitative approach. The object of this research is the implementation of financing management in developing facilities and infrastructure at SMP Hasbunallah. The subjects of this study were the principals and SMP Hasbunallah foundations. The data collection techniques are carried out by means of interviews, observation and documentaries. Data processing techniques using data reduction, data display and data verification and data analysis using descriptive qualitative. The results of this study indicate that the implementation of financing management in developing facilities and infrastructure at SMP Hasbunallah, namely; 1) Financing. All funding has been planned and structured and realized according to existing conditions and needs, especially the needs for the teaching process as well as the process of student learning activities. 2) school facilities and infrastructure; a) The manager has planned the financing of facilities and infrastructure. b) The manager has provided the necessary facilities and infrastructure. c) The manager prepares a storage place for the infrastructure that is held. d) Managers make an inventory of the required facilities and infrastructure. e) School managers also maintain facilities and infrastructure properly and properly with the aim of keeping them longer. f) School administrators jointly organize the existing facilities and infrastructure. g) Managers and teachers and students maintain and maintain the use of existing facilities and infrastructure. h) The manager removes unfit facilities and infrastructure. i) Managers and teachers supervise the use of existing facilities and infrastructure.